2006
DOI: 10.1097/01.ta.0000217271.25809.a0
|View full text |Cite
|
Sign up to set email alerts
|

A Neutrophil Elastase Inhibitor, Sivelestat, Improves Leukocyte Deformability in Patients With Acute Lung Injury

Abstract: NE concentration and neutrophil rigidity are significantly increased in SIRS patients with ALI. Sivelestat appears to reduce NE concentration and neutrophil stiffness and improve pulmonary oxygenation in patients with ALI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…13,14 A specific NE inhibitor, sivelestat sodium hydrate (ONO-5046), is now approved for clinical use on ALI complicated with systemic inflammatory response syndrome in Japan. Although several clinical reports describe the protective effects of ONO-5046 on human ALI associated with systemic inflammatory response syndrome, [15][16][17][18][19] the literature includes no report of a clinical study evaluating the effect of ONO-5046 on ALI complicated with AKI. The present study is designed to elucidate the possible therapeutic effects of a specific NE inhibitor ONO-5046 on ALI induced by AKI using mouse BNx model.…”
mentioning
confidence: 99%
“…13,14 A specific NE inhibitor, sivelestat sodium hydrate (ONO-5046), is now approved for clinical use on ALI complicated with systemic inflammatory response syndrome in Japan. Although several clinical reports describe the protective effects of ONO-5046 on human ALI associated with systemic inflammatory response syndrome, [15][16][17][18][19] the literature includes no report of a clinical study evaluating the effect of ONO-5046 on ALI complicated with AKI. The present study is designed to elucidate the possible therapeutic effects of a specific NE inhibitor ONO-5046 on ALI induced by AKI using mouse BNx model.…”
mentioning
confidence: 99%
“…Varied methods to measure PMN deformability have been reported, 17,18 but we used the method described by Tanaka et al, 8,9,13 which is able to measure PMN deformability at the bedside easily and quickly in a serial fashion and in realtime. Therefore, this strategy might lead to earlier diagnosis of DIC, quick institution of treatment, and the effective monitoring of the response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the relationship between PMN activity and PMN deformability, the abundance of CD11b on the cell Acute Medicine & Surgery 2015; 2: [13][14][15][16][17][18][19][20] Leukocyte deformability in sepsis-induced DIC 17 surface was measured in 11 sepsis-induced DIC patients and five sepsis patients without DIC in this study. Nine healthy volunteers were used as controls.…”
Section: Polymorphonuclear Leukocyte Activity In Patients With Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, experiments have shown its efficacy in animal models of lung injuries caused by endotoxin (6), cobra toxin (7) (which is a complement activator), bleomycin (8), and hydrochloric acid (9,10). Today it is widely used in clinics to improve acute lung injury accompanying systemic inflammatory response syndrome caused by aspiration pneumonia, surgery, injury, and infection (11)(12)(13)(14). Experimental studies have shown that, in the case of radiation-induced lung injury, the immediate release of proinflammatory cytokines such as TNF-α, IL-1 and IL-6 after lung irradiation is closely related with lung toxicity.…”
Section: Introductionmentioning
confidence: 99%